IMPROVING STUDENTS’ PRONUNCIATION OF MONOPHTHONG SOUND IN READING NARRATIVE TEXT BY USING CHORAL READING TECHNIQUE AT THE EIGHTH GRADE STUDENTS OF MTS ALKHAIRAT ALINDAU - Yuli Nursyam; Rusli; Zuhra; Rasmi (English Tadris Department, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Datokarama Palu, 2021)
This research discusses about the use of Choral Reading in reading narrative text. The purpose of this research was to determine whether the choral reading technique affects students' pronunciation. The researcher used a quasi-experimental research design, the population in this research is class VIII Mts Alkahirat Alindau which consists of two classes, they are class 8A and 8B. In this research, class 8B as the Experimental Group by usinga purposive sampling technique. In the experimental class, the researcher gave a pre-test, treatment (choral reading), and post-test, while for the control class, only pretest and post-test without treatment. The researcher collected data through a reading test. From the calculation of the data it showed that the difference in students' scores on the pre-test and posttest with an average post-test score was higher than the average of pre-test score (67.06>30.26). This can be seen from the results obtained before and after the treatment, the score on post-test of experimental class was higher than the score on the pos-test of control group (67.0>51.2). In addition, the result showed that the t-counted was higher than the t-table (52.94>2084. Based on the data analysis, the researcher concluded that the used of Choral Reading technique was affects the pronunciation of the 8th grade students of MTs Alkharat Alinda.